Rezension von: Franz, Gunther, Huberinus, Rhegius, Holbein - Wunder, Gerd (Württembergisch Franken, 1975)
Gunther Franz: Huberinus-Rhegius-Holbein. (Bibiotheca Humanistica et Reformatorica Bd. 7). Nieuwkoopde Graaf 1973. 313 S. 39 Abb. Hfl. 95.-.